La contribución del regadío a la mejora de la renta agraria de los Monegros (Aragón) - Bouzaida, Mohamed Amir; Frutos Mejías, Luisa María (Geographicalia, 2016)
The water shortage is a relative concept and its definition is raising many discussions: some countries can solve this problem through small changes in water management, and others need deeper changes such as in the rnanagement, in the institutional organization and in the investments of the hydraulic infrastructures to enlarge the offer of the water. One of those changes is the agrarian reform as an attempt to resolve solving the social and economic disarrangement linked to the property structure and to the exploitation. The agrarian reform generated by the transformation in irrigated land carried out in the region of Los Monegros used as the study asea, is a paradigmatic sample of these changes. The economic analisis of the cultures, their production and its result will allow to value the contribution and the importance of this reforms in the farmers rent in the region.
Keywords: Los Monegros; agrarian reforms; transformation in irrigated land; farmers rent; socio-economic impact